Late initiation of antenatal care and associated factors among pregnant women in Addis Zemen primary hospital, South Gondar, Ethiopia - Haileab Fekadu Wolde; Adino Tesfahun Tsegaye; Malede Mequanent Sisay (BMC, 2019)
Abstract Background Antenatal care (ANC) is special care for pregnant women with the aim of preventing, detecting and treating health problems in both the fetus and mother. Early ANC attendance promotes early detection and treatment of complications which result in proper management during delivery and puerperium. However, the majority of pregnant women in Ethiopia initiate their ANC late. Therefore, this study aimed to assess the prevalence of late initiation of ANC and its associated factors among attendants in Addis Zemen primary hospital. Method An institution-based cross-sectional study was conducted at Addis Zemen primary hospital from February 7 to June 122,018. The systematic random sampling technique was employed to select 369 pregnant women who attended ANC in the hospital. Data cleaning and analysis was done using SPSS version 25 statistical software. Descriptive statics and bi variable and multivariable logistic regression models were employed to assess the magnitude and factors associated with late initiation of ANC defined as making the first visit after 12 weeks of gestation. Result This study indicated that 52.5% of the attendants initiated ANC late. The multivariable logistic regression analysis showed that being housewife (Adjusted odds ratio (AOR) = 2.85, 95% CI: 1.36, 5.96), self-employment (AOR = 2.38, 95% CI: 1.12, 5.04), travel expenses (AOR = 1.72, 95% CI: 1.05, 2.81), poor knowledge about ANC (AOR = 2.98, 95% CI: 1.78, 5.01) and unplanned pregnancy (AOR = 2.31, 95% CI: 1.28, 4.16) were significantly associated with late ANC initiation. Conclusion The prevalence of late ANC initiation remains a major public health issue in Ethiopia. The major factors for being late were found to be poor knowledge, being housewife, and self-employment, travel expenses and unintended pregnancy. District and zonal health offices should work to create awareness about the importance of early initiation of ANC, make the service closer to the community and increase contraceptive utilization.